Double trouble with triple bubble: A rare case of double small bowel atresia in a neonate - R. Ramanuja Naidu; Mohd Razin Hassan; Wan Mohd Ruzaimie Wan Mohamad Noor; Mohd Tarmizi Md Nor (Elsevier, 2021)
We experienced a rare case of double small bowel atresia (SBA) at our centre. A premature baby boy was born at 35 weeks of gestation. Antenatal scans had already shown a grossly dilated stomach and bowel. Postnatal abdominal X-ray (AXR) showed a triple bubble sign. During emergency laparotomy, we found that there was a Type III atresia at the second part of duodenum and a Type I atresia at the duodenojejunal junction. Duodeno-duodenostomy, duodeno-jejunostomy, duodenal plication and appendicectomy were done. Post-operatively, he was fasted for almost two weeks due to persistently high nasogastric aspirates. However, with the help of prokinetic drugs, he was finally able to tolerate breast feeding and was discharged home well.